Ḵẖulq-i ʻaẓīm : yaʻnī, aḵẖlāqī maz̤āmīn par aḥādīs̲-i Nabavī kā ek mukammal majmūʻah maʻ tarjamah-yi Urdū - Walī Allāh al-Dihlawī, 1702 or 3-1762 or 3. (SAMP early 20th-century Indian books project, 1926)
Collection of articles on Islamic etiquette.